Edith Stein: Faith as Decision. Some Thoughts Inspired by Augustine, Descartes, Husserl, Ingarden and Benedict XVI. - Jędraszewski, Marek (Filozofia Chrześcijańska, 2013)
There are two components of an act of religious faith: human will and God as truth and the Lord. Stein abandons Husserl’s phenomenological reduction in the definition of human “self” for the sake of the influence of God, who shapes human “self”. She stresses the role of the will besides of the mind. The will decides whether “self” can be shaped by God or not. In this way Stein favors Augustine’s understanding of “self” ascribing to the will the leading role in process of finding truth about “self”.